Strength Based Skill Training Untuk Peningkatan Kekuatan Harapan Siswa - Asti Siti Aminah; Ilfiandra Ilfiandra; Ipah Saripah (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2020)
Strength of hope defineted as a positive motivational state that obtained from an interactive derived sense of successful agency (goal-directed energy), and pathways (planning to meet goals). The study used a qualitative aproach with narrative methods and One Project before-and-after design. The result of the research finds that strength based skill training can result in increased strength of hope from students through the characteristics of high agency and pathway thinking in participants. In general, strength of hope in student has greater aspect on agency or the motivation to achieve happiness in family and social support.